Inhibition of Indoleamine-2, 3-dioxygenase (IDO) in Glioblastoma Cells by Oncolytic Herpes Simplex Virus. (13th August 2012) - Reinhart, Bonnie; Mazzacurati, Lucia; Forero, Adriana; Hong, Chang-Sook; Eguchi, Junichi; Okada, Hideho; Fellows, Wendy; Niranjan, Ajay; Cohen, Justus B.; Glorioso, Joseph C.; Grandi, Paola
Abstract : Successful oncolytic virus treatment of malignant glioblastoma multiforme depends on widespread tumor-specific lytic virus replication and escape from mitigating innate immune responses to infection. Here we characterize a new HSV vector, JD0G, that is deleted for ICP0 and the joint sequences separating the unique long and short elements of the viral genome. We observed that JD0G replication was enhanced in certain glioblastoma cell lines compared to HEL cells, suggesting that a vector backbone deleted for ICP0 may be useful for treatment of glioblastoma. The innate immune response to virus infection can potentially impede oncolytic vector replication in human tumors. Indoleamine-2, 3-dioxygenase (IDO) is expressed in response to interferon γ (IFN γ ) and has been linked to both antiviral functions and to the immune escape of tumor cells. We observed that IFN γ treatment of human glioblastoma cells induced the expression of IDO and that this expression was quelled by infection with both wild-type and JD0G viruses. The role of IDO in inhibiting virus replication and the connection of this protein to the escape of tumor cells from immune surveillance suggest that IDO downregulation by HSV infection may enhance the oncolytic activity of vectors such as JD0G.